Breakfast : the most important book about the best meal of the day (Oxmoor House,an imprint of Time Inc. Books, 2018)
Breakfast is an exploration of everything about breakfast and brunch. This celebration of the most popular meal of the day offers engaging stories, essential how-tos, and killer breakfast recipes. Discover exciting new ingredients and the secrets to making Entenmann's Cake Doughnuts and Taco Bell Crunchwraps at home, among many other dishes. Learn the origins of scrapple and how to brew barista-level drinks. Based on the popular website ExtraCrispy.com, this book--the perfect gift for anyone who loves all-day-breakfast--is packed with 100 photos, humorous illustrations, and amazing, craveable food.